EFFICIENCY AND SAFETY ASSESSMENT OF GENERIC ATORVASTATINE IN PATIENTS WITH HYPERLIPIDEMIA - J. E. Semyonova; S. Y. Martsevich; N. V. Perova; A. M. Olferiev; N. P. Kutishenko; N. Y. Ivanenkova; N. A. Dmitrieva; A. A. Serazhim (Столичная издательская компания, 2015)
Aim. To assess in a short-term study efficiency and safety of hypolipidemic therapy with atorvastatine generic, Tulip, in comparison with simvastatine generic, Vasilip, in hyperlipidemic patients.Material and methods. Open, randomized, comparative, cross over study included 87 patients with hyperlipidemia, who didn't receive hypolipidemic drugs within 6 weeks, or followed hypolipidemic diet for 4 weeks. Each patient received therapy with one of the studied drugs within 6 weeks. Then after 4-week wash-out period the second therapy with the other drug was held. Consequence of courses with each drug was set by randomization. Initial dose of both drugs was 10 mg daily. Dose was adjusted after 3 weeks. The dose was increased to 20 mg daily if cholesterol of low density lipoproteid (CLDL) hadn't reached target level (< 115 mg/dl). of Treatment safety was assessed on the basis of clinical data, hepatic enzymes activity and creatine phosphokinase levels.Results. It is shown, that to reach target figures of plasma lipid spectrum, Vasilip dose was increased significantly more often, than Tulip dose. Average Tulip dose after titration was 14,8 mg daily, Vasilip dose - 15,6 mg daily. Patients with initially higher level of triglycerides (TG > 170 mg/dl) after 6 weeks with Tulip treatment showed TG reduction by 38% and with Vasilip treatment - by 20%. Both drugs showed good tolerance, no significant differences in number of side-effects were observed.Conclusion. 6-week treatment with atorvastatine generic Tulip shows significant hypolipidemic effect, which appears in significant reduction of CLDL, total cholesterol, TG compared to the initial levels. Degree of total cholesterol reduction is significantly higher with Tulip treatment compared to Vasilip treatment. Analyses shown that target levels of the assessed figures were reached in more patients, treated with Tulip. Side-effects in Tulip treatment were not severe.